Kewenangan Pemerintah Dalam Pembubaran Organisasi Masyarakat (Studi Kasus FPI) Dikaitkan dengan Undang-Undang Nomor 16 Tahun 2017 tentang Organisasi Kemasyarakatan - Triyudiana, Andra (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
Religion is a holy thing that should not be interfered with to gain certain interests. "Violence and hatred in the name of God is an act that absolutely cannot be justified." Religion is a holy thing that should not be interfered with to gain certain interests. "Violence and hatred in the name of God is an act that absolutely cannot be justified." In Indonesia itself, the issue of radicalism is often ridden by community organizations (Ormas) to gain their interests. Even though these community organizations or mass organizations are a form of freedom of association, assembly, and expression of opinions are part of human rights in the life of the nation and state. The research conducted is research with normative juridical type. The method considers that the starting point for preparing an analysis of the relevant laws and regulations as well as the applicable regulations relating to Community Organizations. A community organization that is established must not conflict with the state constitution because the constitution is the highest legal umbrella in this country which is the basis for the life of the state. this social organization is a mandate of the 1945 Constitution of the Republic of Indonesia Article 28E paragraph (3). Because one of the objectives of the formation of this social organization is none other than to maintain and preserve norms, values and ethics in the life of society, nation and state whose output is community empowerment in this country.